Lithium Augmentation Versus Citalopram Combination in Imipramine-Resistant Major Depression: A 10-Week Randomized Open-Label Study. Issue 3 (May 2019) - Navarro, Víctor; Boulahfa, Ilham; Obach, Amadeu; Jerez, Dídac; Diaz-Ricart, Maribel; Gastó, Cristóbal; Guarch, Joana
Abstract: Purpose/Background: According to available international clinical guides, tricyclic antidepressants are our first- or second-line treatment of choice for severe unipolar major depression. However, the therapeutic option after an unsuccessful response to a tricyclic antidepressant drug in unipolar major depression is still unclear. Methods/Procedures: This 10-week randomized open-label study assessed the effectiveness of add-on lithium (adjusted to plasma levels) compared with add-on citalopram (30 mg/d) in 104 severe unipolar major depressive patients after a 10-week unsuccessful imipramine (adjusted to plasma level). Efficacy analyses examined changes in the severity of depression symptoms from baseline visit to endpoint and the comparative remission rate between treatment subgroups. Findings/Results: The randomized sample consisted of 104 imipramine-resistant severe unipolar major depressed patients. Both, the percentage of remitters (40.4% vs 21.1%, P = 0.034) and the mean reduction of the Hamilton Depression Rating Scale score (58.8% vs 42.5%, P = 0.005) were significantly greater in the add-on citalopram subgroup at endpoint visit. Implications/Conclusions: Although we should be cautious about generalizing these results to patients with a less severe unipolar major episode, results from the present study suggest that add-on citalopram is a very effective treatment option in unipolar major depressive episodes after an unsuccessful imipramine regimen.